Polystyrene‐Supported Core–Shell Beads with Aluminium MOF Coating for Extraction of Organic Pollutants. Issue 20 (29th July 2019) - Kuo, Yu‐Ching; Pal, Souvik; Li, Fang‐Yu; Lin, Chia‐Her
Abstract: Aluminium‐based metal–organic framework (MOF) coatings on polystyrene bead surfaces were easily synthesized by reacting an intermediate metal hydroxide coating with an organic linker. Several different sizes of polystyrene beads were coated with aluminium metal hydroxide to construct Al@PS core–shell bead materials. The activated Al@PS core–shell beads were involved to make a homogenous MOF‐based layer in the presence of the organic linker. By using different sizes of the PS support the size of MOFs on the PS composites could be fine‐tuned under specific reaction conditions. MOF‐coated core–shell bead materials (Al‐1, 4‐NDC@PS and MIL‐53(Al)@PS) were characterized using various analytical techniques. Al‐1, 4‐NDC@PS and MIL‐53(Al)@PS were evaluated for solid‐phase microextraction (SPME) of hydrophobic polycyclic aromatic hydrocarbons (PAHs) and hydrophilic non‐steroidal anti‐inflammatory drugs (NSAIDs), respectively. Al‐1, 4‐NDC@PS‐1000 displayed high extraction recoveries ranging from 79.2 % to 99.8 % in the SPME of PAHs. Meanwhile, MIL‐53(Al)@PS‐1000 showed 85.9–99.0 % extraction recoveries in the SPME of NSAIDs. These results show that the proposed approach holds potential to extract organic analytes on an industrial scale. Abstract : P.S . An unprecedented approach of aluminium‐based metal–organic framework (MOF) coatings on polystyrene (PS) bead surface materials as core–shell composites is reported. The new PS‐MOF core–shell composites have a controlled spherical size and thin porous MOF layer. The composites of an optimized size display a high performance for solid‐phase microextraction (SPME) of hydrophobic polycyclic aromatic hydrocarbons (PAHs) and hydrophilic non‐steroidal anti‐inflammatory drugs (NSAIDs), respectively.